Phytomedicine in 21st century: challenges, innovations & future directions - Mohd. Wasiullah; Piyush Yadav; Hariom Pandey (International Journal of Tropical Medicines, 2025)
Phytomedicine, the use of plant-derived substances for therapeutic purposes, has experienced significant advancements and challenges in the 21st century. This review explores the current state of phytomedicine, highlighting its advantages, such as natural ingredients, fewer side effects, and cultural acceptance, as well as its disadvantages, including variable quality, lack of standardization, and limited research. The challenges faced by phytomedicine are discussed, focusing on issues of standardization, regulatory discrepancies, scientific evidence gaps, interactions and safety concerns, sustainability, and ethical considerations. Recent innovations in the field are presented, including advanced extraction technologies, pharmacogenomics, synthetic biology, omics technologies, and integrated therapeutic approaches. The future directions of phytomedicine are outlined, emphasizing enhanced research, personalized medicine, integration with conventional treatments, sustainable practices, technological advancements, data-driven approaches, global collaboration, community involvement, and ethical and regulatory progress. The review concludes that by addressing current challenges and leveraging groundbreaking innovations, phytomedicine has the immense potential to make substantial contributions to global health in the 21st century.The ongoing evolution of the field, driven by rigorous research, technological advancements, and a commitment to sustainability and ethics, will ensure that plant-based therapies continue to play a vital role in modern healthcare.
Keywords: Herbal supplements; Phytomedicine; Plant extracts; Plant-based therapies; essential oils